MOTIVASI INDUSTRI PERHOTELAN DALAM MENERAPKAN KONSEP ECOPRENEURSHIP: STUDI KASUS PADA HOTEL – HOTEL KAWASAN ITDC NUSA DUA BALI - Putu Ratih Pertiwi (Jurnal Ilmiah Hospitality Management, 2017)
An eco-friendly business model as the implementation of ecopreneurship concept is a form of a business attitude, which has a commitment due to sustainable development concept. Nowadays we could see that almost all of the hotel industries all over the world contributing to eco-friendly business campaign. Those hotels have various yet strong reasons in order to address their awareness by implementing the concept of ecopreneurship to their business. The focus of this paper is to examine the motivation of stars hotel in ITDC Nusa Dua Bali in implementing the concept of ecopreneurship in their business, as well as the benefits and the obstacles encountered by them. Analyzed using descriptive qualitative analysis technique where the research stages are started from the literature review related to the concept of ecopreneurship integrated into hotel business, data collection, then identifying the motivation, benefits, and obstacles encountered by stars hotel in ITDC Nusa Dua Bali in implementing the concept of ecopreneurship to their business. The result of this paper could be used as the references for the hotel industries in applying the concept of ecopreneurship into their business.